First Report of Lelliottia amnigena Causing Soft Rot on Purple Stem Mustards in China - Li, Junhui; Qin, Shiyang; Shi, Yanxia; Xie, Xuewen; Chai, A Li; Wang, Yuanhong; Li, Baoju; Li, Lei (Plant disease, 2025)
The purple stem mustards (Brassica rapa subsp. chinensis var. purpuraria) (Govaerts R, 2003) are widely cultivated along Yangtze River Valley in China, which is famous for its flavorful and nutritious edible stalks (Wang et al., 2022). In February 2023, a disease of soft rot was observed in multiple purple stem mustards planting fields in Wuhan city, Hubei province, China (30.41°N, 114.22°E). Disease incidence rates were almost 20 to 30% in the planting area (5 ha in size), causing severe economic loss. Infected plants displayed water-soaked symptoms at the base of the petioles, emitting a foul soft rot odor. The severely infected petioles, stems and roots exhibit pus symptoms leading to plant death. To identify the causal agent, small pieces of soft rot symptomatic tissue were cut from the margin of necrotic lesions and surface disinfected with 75% (v/v) ethanol for 30 seconds, followed by three successive rinses with sterile distilled water. The exudates from the clipped tissues were serially diluted and then incubated onto nutrient agar (NA) plates to obtain purified strains at 28°C for 48 hours (Koike et al., 2002). After incubation, 15 strains were obtained and the colonies of all strains were Gram-negative, aerobic, small, round, convex, whitish to dull white, and had smooth slimy edges. Three single bacterial strains CT020801 - CT020803, which were individually isolated from three different diseased samples, were selected as representative strains for further study. Biochemical tests using the BIOLOG GENIII microplate system (Biolog, Hayward, CA, USA) revealed that these strains were positive for methyl red, pectin, dextrin, D-Cellobiose, β-galactosidase, citrate, and maltose, but negative for indole, arginine dihydrolase, urease, ornithine decarboxylase, and gelatinase tests. The 16S ribosomal RNA gene and the three housekeeping genes, atpD, rpoB, and recN were amplified using genomic DNA of Lelliottia amnigena NCTC12124T as the template, with specially designed primers. All amplified fragments were sequenced and deposited in GenBank with accession numbers OQ954706-OQ954707, OQ954713, and OQ953873-OQ953881. BLAST alignments of the 16S rRNA, atpD, rpoB and recN sequences revealed that the sequences of Strain CT020801-03 exhibited the highest identity (100%, ≥97.97%, ≥98.85% and ≥94.52%, respectively) with L. amnigena （Figure S2）. Phylogenetic tree analysis based on multilocus sequence joint 16S rRNA - atpD - rpoB - recN revealed that CT020801 - CT020803 and L. amnigena clustered together in the same clade (Carrie et al., 2013). These results were consistent with those reported for Lelliottia amnigena (Osei et al., 2022). To confirm pathogenicity, healthy base petioles of three-week-old purple stem mustards seedlings were stab inoculated with 20 μL bacterial suspensions (approximately 108 CFU/mL) and then incubated at 28°C and 80% relative humidity in a growth chamber. A sterile liquid NB medium served as the negative control. The test was repeated thrice with each test consisting of five seedlings per treatment. After three days, soft rot symptoms appeared on the stem bases of the inoculated plants, consistent with the initial symptoms observed in the field. Control plants showed no symptoms. The strains were successfully re-isolated from symptomatic plants and identified as L. amnigena, fulfilling Koch's postulates. L. amnigena, a member of the Enterobacter genus (Birlutiu et al., 2023; Brady et al., 2013; Izard et al., 1981), is commonly found in soil and has been identified as an opportunistic pathogen responsible for plant soft rot disease (Reyes-García et al., 2020; Schroeder et al., 2009; Wu et al., 2023). Previous studies have linked L. amnigena to soft rot disease in potato tubers in China. However, this study marks the first documented case of L. amnigena causing soft rot disease in purple stem mustards in China. This discovery expands the known host range of the pathogenic bacteria and will help to provide essential information for making effective measures to manage this disease.